Antinociceptive profile of (-)-spectaline: A piperidine alkaloid from Cassia leptophylla - Alexandre-Moreira, M. S.; Viegas, C.; de Miranda, ALP; Bolzani, Vanderlan da Silva [UNESP]; Barreiro, E. J. (Georg Thieme Verlag Kg, 2003)
The antinociceptive activity of (-)-spectaline (1), a piperidine alkaloid isolated from Cassia leptophylla Vog. (Leguminosae), was investigated. We have also studied the acute oral toxicity of 1 in mice and it did not show any signals of toxicity in doses lower than 400 mumol/kg. The antinociceptive effect of 1 was evaluated on chemical (acetic acid, formalin and capsaicin) and thermal (hot plate and tail flick) pain models in mice, using classical standard drugs. Dipyrone ID50 = 14.68 mumol/kg (4.8 mg/kg), in-domethacin ID50 = 0.78 mumol/kg (0.28 mg/kg) and (-)-spectaline ID50 = 48.49 mumol/kg (15.75 mg/kg), all produced a significant inhibition of acetic acid-induced abdominal writhing in mice. (-)-Spectaline was inactive in the hyperalgesic model of formalin and did not show any central analgesic activity (hot plate and tail flick models). In the capsaicin-induced neurogenic pain model, (-)-spectaline presented an important inhibitory effect with an ID50 = 20.81 mug/paw and dipyrone ID50 = 19.89 mug/ paw. The ensemble of results permitted us to identify 1 as an antinociceptive compound. The mechanism underlying this antinociceptive effect of 1 remains unknown, but the results suggest that such an effect could be related to pathways associated to vanilloid receptor systems.
Keywords: Cassia leptophylla vog.; Leguminosae; (-)-spectaline; antinociceptive